Measuring PV Module Performance at Different Tilt Angles in Southern Iraq Based Simulation - Salam T. Hussain, Abadal (International Journal of Engineering and Technology, 2018)
This paper presented that how to calculate the tilt angles and solar irradiance on photovoltaic (PV) module in southern Iraq (latitude 30° N). The latitude and day number of the city is taken into account to calculate the tilt angle and solar irradiance by using a mathematical equation. The optimum tilt angles of PV module in southern Iraq are range from 38° to 84°. The yearly maximum total and average solar irradiance is needed to determine the optimum tilt angle of PV module. The result shows that 50° of tilt angle is the best performance of PV module in southern Iraq.